The transmembrane protein LRIG2 increases tumor progression in skin carcinogenesis. Issue 11 (21st October 2019) - Hoesl, Christine; Fröhlich, Thomas; Hundt, Jennifer E.; Kneitz, Hermann; Goebeler, Matthias; Wolf, Ronald; Schneider, Marlon R.; Dahlhoff, Maik
Abstract : Over the last few decades, the number of cases of non‐melanoma skin cancer (NMSC) has risen to over 3 million cases every year worldwide. Members of the ERBB receptor family are important regulators of skin development and homeostasis and, when dysregulated, contribute to skin pathogenesis. In this study, we investigated leucine‐rich repeats and immunoglobulin‐like domains 2 (LRIG2), a transmembrane protein involved in feedback loop regulation of the ERBB receptor family during NMSC. LRIG2 was identified to be up‐regulated in various types of squamous cell carcinoma (SCC), but little is known about LRIG2 in cutaneous SCC (cSCC). To investigate the function of LRIG2 in cSCC in vivo, we generated a skin‐specific LRIG2 overexpressing transgenic mouse line (LRIG2‐TG) using the Tet‐Off system. We employed the 7, 12‐dimethylbenz(a)anthracene/12‐O‐tetra‐decanoylphorbol‐13‐acetate (DMBA/TPA) two‐stage chemical carcinogenesis model and analyzed the skin during homeostasis and tumorigenesis. LRIG2‐TG mice did not exhibit alterations in skin development or homeostasis but showed an interaction between LRIG2 and thrombospondin‐1, which is often involved in angiogenesis and tumorigenesis. However, during carcinogenesis, transgenic animals showed significantly increased tumor progression and a more rapid development of cSCC. This was accompanied by changes in the ERBB system. After a single TPA application, inflammation of the epidermis was enhanced during LRIG2 overexpression. In human skin samples, LRIG2 expression was identified in the basal layer of the epidermis and in hair follicles of normal skin, but also in cSCC samples. In conclusion, epidermal LRIG2 excess is associated with activated EGFR/ERBB4‐MAPK signaling and accelerated tumor progression in experimentally induced NMSC, suggesting LRIG2 as a potential oncoprotein in skin. Abstract : To study the transmembrane protein leucine‐rich repeats and immunoglobulin‐like domains 2 (LRIG2), we overexpressed LRIG2 skin‐specifically in mice. Epidermal LRIG2 excess is associated with activated EGFR/ERBB4‐MAPK signaling, inactivation of the tumor suppressor PTEN, and accelerated tumor progression with a more rapid development of cutaneous squamous cell carcinoma in experimentally induced non‐melanoma skin cancer, suggesting LRIG2 as a potential oncoprotein in skin.